PENGARUH PUPUK HAYATI DAN TANAMAN JARAK PAGAR (Jatropha curcas L.)TERHADAP PENYERAPAN LOGAM BERAT TEMBAGA (Cu) DAN TIMBAL (Pb) PADA LAHAN BERPASIR - Sudaryono . (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
In general, coastal areas have the physical and chemical properties of lessfertile land with an extreme dry climate, so that only a few plants that can live,including Jatropha curcas L. To enhance fertility and improve soil physicalproperties, need the addition of organic fertilizer. Source of compost canbe derived from a variety of wastes, including household waste and landfill.Quality compost landfill taken from Piyungan, Yogyakarta, has a high content of organic C, pH neutral, low N concentration, with the ratio C/N is very high. But compost landfill has an obstacle in the form of heavy metal containing high Cu and Pb. To prevent accumulation heavy metals into plant tissue or clean up heavy metals from the soil it was attempted by phytoremediation using jatropha plantation and bio-fertilizer that contains bacteria Azotobacter sp and Pseudomonas sp.From the research results can be informed that: (1) The city compost and biological fertilizers, can increase soil fertility with increasing nutrient content in soil. (2) Biofertilizers could inhibit the accumulation of copper (Cu) and lead (Pb) into Jatropha curcas L., (3)Jatropha plant can be classified as phytoremediation plants, because it can absorption heavy metals into leaf tissue.Key words: landfill compost , bio fertilizer, jatropha plants, heavy metals